STUDY OF GLOBAL WARMING POTENTIAL IMPACT FROM MUNICIPAL SOLID WASTE MANAGEMENT USING BIOCONVERSION OF BLACK SOLDIER FLY (Hermetia illucens): CASE STUDY DEPOK CITY - R. Muchamad Irchas Sukabudhi; Nastiti Siswi Indrasti; Andes Ismayana (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
This research comprehensively investigated the global warming potential impact of the municipal solid waste management system using bioconversion of black soldier fly (Hermetia illucens). For this purpose, the life cycle assessment methodology was applied to evaluate the global warming potential over a 100-year horizon (GWP100) for the system used by XYZ Ltd. Depok City, identify emission sources and analyze alternative strategies to mitigate environmental impacts. Data collection for this study was conducted at XYZ Ltd. in Depok City, West Java Province, between May and June 2022. This case study focused on a cradle-to-gate analysis with a functional unit of 1 ton of municipal solid waste. The impact assessment results showed that GWP100 impact from bioconversion of municipal solid waste was 3.69E+02 kg CO2 eq. Solid waste disposed through open dumping was a dominant contributor of these emissions (2.57E+02 kg CO2 eq). The GHG emissions that were the primary source of these impacts are CH4 (2.47E+02 kg CO2 eq) and CO2 (1.19E+02 kg CO2 eq). Ultimately, the improvement scenarios recommended in this study are the pretreatment of municipal solid waste, substituting photovoltaic electricity use, choosing priority clients with the closest distance, and substituting biocomposite packaging. Implementing these measures will reduce the GWP100 impact by 56.02%. Keywords: BSF bioconversion; global warming potential; Hermetia illucens; LCA; Municipal solid waste